Incidence of bleeding in 8172 percutaneous ultrasound-guided intraabdominal diagnostic and therapeutic interventions - results of the prospective multicenter DEGUM interventional ultrasound study (PIUS study) - Strobel, Deike; Bernatik, T.; Blank, W.; Will, U.; Reichel, A.; Wuestner, M.; Keim, V.; Schacherer, D.; Barreiros, A. P.; Kunze, G.; Nuernberg, D.; Ignee, A.; et al. (Ultraschall in der Medizin, 2015)
To analyse the incidence of bleeding after percutaneous ultrasound guided diagnostic and therapeutic intraabdominal interventions in a prospective multicentre study (DEGUM percutaneous interventional ultrasound study).Within a time period of 2 years diagnostic and therapeutic intraabdominal interventions (with the exclusion of ascites paracentesis) performed percutaneously under continuous ultrasound (US) guidance were prospectively assessed using a pseudonymized standardized web site entry form. Number and type of intervention, operator experience, patient characteristics, medication, lab data as well as technical aspects of the procedure and bleeding complications were analysed according to the interventional radiology standards.8172 US-guided intraabdominal interventions (liver n = 5903; pancreas n = 501, kidney n = 434, lymph node = 272, biliary system n = 153, spleen n = 63, other abdominal organs and extra-organic targets n = 999) were analysed in 30 hospitals. The majority were diagnostic biopsies including 1780 liver parenchyma, 3400 focal liver lesions and 404 pancreatic lesions. 7525 interventions (92.1 %) were performed in hospitalized patients (mean age 62.6 years). Most operators were highly experienced in US-guided interventions (> 500 interventions prior to the study n = 5729; 70.1 %). Sedation was administered in 1131 patients (13.8 %). Needle diameter was >= 1 mm in 7162 punctures (87.9 %) with main focus on core needle biopsies (18 G, n = 4185). Clinically relevant bleeding complications with need of transfusion (0.4 %), surgical bleeding control (0.1 %) and radiological coiling (0.05 %) were very rare. Bleeding complications with fatal outcome occurred in four patients (0.05 %). The frequency of major bleeding complications was significantly higher in patients with an INR > 1.5 (p < 0.001) and patients taking a medication potentially interfering with platelet function or plasmatic coagulation (p < 0.0333).This prospective multicentre study confirms the broad spectrum of percutaneous US-guided intraabdominal interventions. However diagnostic liver biopsies dominate with the use of core needle biopsies (18 G). Percutaneous US-guided interventions performed by experienced sonographers are associated with a low bleeding risk. Major bleeding complications are very rare. A pre-interventional INR < 1.5 and individual medication risk assessment are recommended.
EVALuna2:2035